2008
DOI: 10.1016/j.bbamem.2007.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial pre-transmembrane domains in viral proteins promoting membrane fusion and fission

Abstract: Membrane fusion and fission underlie two limiting steps of enveloped virus replication cycle: access to the interior of the host-cell (entry) and dissemination of viral progeny after replication (budding), respectively. These dynamic processes proceed mediated by specialized proteins that disrupt and bend the lipid bilayer organization transiently and locally. We introduced Wimley-White membrane-water partitioning free energies of the amino acids as an algorithm for predicting functional domains that may trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 133 publications
(232 reference statements)
3
88
0
1
Order By: Relevance
“…This longer membrane-suitable region is observed for the PIV5 C-term-TM and contributes to fusion (57). It is also observed in other viruses such as influenza (51) and HIV, where shortening the length of C-term-TM helices can halt the fusion process (79,80). Fig.…”
Section: Discussionmentioning
confidence: 78%
“…This longer membrane-suitable region is observed for the PIV5 C-term-TM and contributes to fusion (57). It is also observed in other viruses such as influenza (51) and HIV, where shortening the length of C-term-TM helices can halt the fusion process (79,80). Fig.…”
Section: Discussionmentioning
confidence: 78%
“…This implies that peptides recreating its native structure might in principle compose stand-alone HIV vaccines (6,13,19,20,72,73). Although intensively studied, data supporting the structural MPER connectivity within a synthetic peptide vaccine were lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Given its proximity to the envelope surface and the unusual concentration of aromatic residues, it has been proposed that structuring coupled to membrane partitioning may play a crucial role in determining the structure and orientation of MPER epitopes, which in turn will have an impact on immunogenicity (19,62,72,83). Thus, we studied in parallel the MPERp structure and immunogenicity in two different liposomal formulations (Figs.…”
Section: Figure 8 Recovered Responses After Vaccination With the Popmentioning
confidence: 99%
“…[26][27][28][29][30] Liposomes have been successfully used in the delivery of bioactive proteins into flagellated E. coli envelope, 31 and to transfect competent E. coli and Mycoplasma capricolum cells with encapsulated plasmid DNA. 32,33 By using liposomes made of lipid extracts from the whole bacterial membranes of Salmonella minnesota RE595 (the composition and lipids were not identified), Tomlinson et al 33 successfully incorporated phospholipid and proteins into gram-negative bacteria and confirmed that a fusion process was involved in this extensive phospholipid transfer.…”
Section: Discussionmentioning
confidence: 99%